Current knowledge of SLC6A1-related neurodevelopmental disorders. Issue 2 (13th October 2020) - Goodspeed, Kimberly; Pérez-Palma, Eduardo; Iqbal, Sumaiya; Cooper, Dominique; Scimemi, Annalisa; Johannesen, Katrine M; Stefanski, Arthur; Demarest, Scott; Helbig, Katherine L; Kang, Jingqiong; Shaffo, Frances C; Prentice, Brandon; et al.
Abstract: Advances in gene discovery have identified genetic variants in the solute carrier family 6 member 1 gene as a monogenic cause of neurodevelopmental disorders, including epilepsy with myoclonic atonic seizures, autism spectrum disorder and intellectual disability. The solute carrier family 6 member 1 gene encodes for the GABA transporter protein type 1, which is responsible for the reuptake of the neurotransmitter GABA, the primary inhibitory neurotransmitter in the central nervous system, from the extracellular space. GABAergic inhibition is essential to counterbalance neuronal excitation, and when significantly disrupted, it negatively impacts brain development leading to developmental differences and seizures. Aggregation of patient variants and observed clinical manifestations expand understanding of the genotypic and phenotypic spectrum of this disorder. Here, we assess genetic and phenotypic features in 116 individuals with solute carrier family 6 member 1 variants, the vast majority of which are likely to lead to GABA transporter protein type 1 loss-of-function. The knowledge acquired will guide therapeutic decisions and the development of targeted therapies that selectively enhance transporter function and may improve symptoms. We analysed the longitudinal and cell type-specific expression of solute carrier family 6 member 1 in humans and localization of patient and control missense variants in a novel GABA transporter protein type 1 protein structure model. In this update, we discuss the progress made in understanding and treating solute carrier family 6 member 1-related disorders thus far, through the concerted efforts of clinicians, scientists and family support groups. Abstract : Genetic variants in the SLC6A1 gene have been identified as a monogenic cause of neurodevelopmental disorders, including epilepsy with myoclonic atonic seizures, autism spectrum disorder and intellectual disability. Here, we assess the genetic and phenotypic features observed in 116 patients with SLC6A1 variants. Graphical Abstract: